PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DALAM PENGAJARAN MATEMATIKA PADA MAHASISWA S1 ILMU KEOLAHRAGAAN - Nur Syamsiyah, (Jurnal Penelitian Pendidikan Matematika dan Sains, 2008)
Mathematics is one of basic science that has important contribution in science and technology masteries, not aside from science and technology of sport, even its applied or reasoning aspect. As basic of science and technology of sport, mathematics is taught to S-1 IKOR students.By jigsaw type cooperative learning every student is given responsible to understand the subject that has been determined because every student has to take a part and active in learning process in order the students have more motivation in learning so their ability in mathematics improves.The research questions in this study are : jigsaw type cooperative learning can improve S-1 IKOR students ability in mathematics has not been proven, and the students have been given jigsaw type cooperative learning get more ability improving in mathematics than the students have been given traditional learning has not been proven. In order to answer the questions, the researchers have already done ady on S-1 IKOR students class 2008 B and C amount 46 students as experiment group and class 2008 A amount 36 students as control group. The subject that is choosen for this research is trigonometry. This study uses  non randomized control group pretest-posttest design.The result of the study shows that there is an improvement of the score in the experiment group (the group which has been given jigsaw type cooperative learning), from the average score ( 60,47 ±  7,43) in the pretest increase to (65,86 ± 7,47) in the posttest. The result of data analysis using SPSS shows that t calculation (11,054) > (1,881) t table, in this case H0 is rejected. It can be concluded that jigsaw type cooperative learning can improve S-1 IKOR students ability on mathematics.There is also a difference on the improvement of the ability between experiment group and control group (which is given traditional learning). The first group shows a higher improvement, the average score is (12,15 ± 7,46), compare to the second group whose average score is (5,00 ± 3,39). The data analysis result shows that t calculation (5,335) > (1,800) t table, H0 is rejected. It can be concluded that the students have been given jigsaw type cooperative learning get more ability improving in mathematics than the students have been given traditional learning.